Analytical Solution for Differential and Nonlinear Integral Equations via Fϖe-Suzuki Contractions in Modified ϖe-Metric-Like Spaces. (15th February 2021) - Hammad, Hasanen A.; De la Sen, Manuel; Aydi, Hassen
Abstract : The aim of this manuscript is to present a new space, namely, a modified ϖ e -metric-like space, and we establish some related fixed point results using extended F ϖ e -Suzuki and generalized F ϖ e -Suzuki contractions on the mentioned space. Here, we support our theoretical consequences in two ways: the first one consists of presenting illustrative examples and the second one consists of finding analytical solutions for some integral and differential equations in the context of the mentioned space.